A MULTIDIMENSIONAL ANALYTICAL FRAMEWORK FOR EDUCATION POLICY IMPLEMENTATION: A CONCEPTUAL ENRICHMENT OF MATLAND’S TYPOLOGY - Ferli Yuledi; Anna Gustina Zainal; Noverman Duadji; Suripto (Adisam Publisher, 2026)
Indonesia’s zoning-based admission policy and its Kurikulum Merdeka reform both illustrate the same problem, a single national design produces uneven results once it reaches the district level, with school quality gaps, uneven teacher readiness, and variable local government backing each shaping how different areas carry the policy out. Matland’s ambiguity-conflict typology (1995) explains this kind of variation by reading implementation outcomes through two dimensions, the clarity of a policy’s objectives and the degree of conflict among the actors responsible for carrying it out. Applied to Indonesian basic education, a policy field crowded with actors and heavily dependent on local government backing that varies across districts, the two-dimensional model reaches its limit quickly, because the variation on the ground comes from a wider set of forces than two axes alone can capture. This article builds outward from that limit into a framework of six determinant dimensions, institutional capacity, inter-actor collaboration, policy entrepreneurship, political support, community participation, and local wisdom, drawn respectively from New Institutionalism, Collaborative Governance, Policy Entrepreneurship, and Local Wisdom Theory, which together account for how a policy’s ambiguity and conflict translate into outcomes on the ground. Indonesia’s Drug Abuse Prevention and Eradication Policy, P4GN, tests the framework across four research areas in Lampung Province, since it shares education’s multi-actor, locally contingent character and produces the same kind of uneven outcomes the six dimensions are built to explain. From there, the discussion turns to what that configuration means for district-level Kurikulum Merdeka implementation and zoning, tracing how the six dimensions play out under different institutional and political conditions. This expanded set of criteria allows the framework to move beyond the ambiguity-conflict dichotomy and provides researchers a device for accounting for why the same national policy can have such different impacts within different districts. implementation of education policies, Matland typology, multidimensional analysis framework, PPDB zoning, and the Merdeka Curriculum. This wider set of elements allows the paradigm to go beyond the ambiguity-conflict dichotomy and provides researchers an explanation of why one national policy can have such different effects in districts.